FDTD simulation of antenna coating effects on the radiation properties of cellular phones - Al-Sunaidi, M. A. (1999)
A detailed characterization of the effects of antenna coating on the performance of cellular phones is presented. The FDTD-based simulations show that antenna coating facilitates the reduction of the antenna length without jeopardizing the radiation properties of the antenna. However, the radiation efficiency is slightly affected.